Calcium-calmodulin kinase II mediates digitalis-induced arrhythmias - Gonano, Luis Alberto (2011)
Digitalis-induced Na(+) accumulation results in an increase in Ca(2+)(i) via the Na(+)/Ca(2+) exchanger, leading to enhanced sarcoplasmic reticulum (SR) Ca(2+) load, responsible for the positive inotropic and toxic arrhythmogenic effects of glycosides. A digitalis-induced increase in Ca(2+)(i) could also activate calcium-calmodulin kinase II (CaMKII), which has been shown to have proarrhythmic effects. Here, we investigate whether CaMKII underlies digitalis-induced arrhythmias and the subcellular mechanisms involved.